(untitled) (Revista Brasileira de Contabilidade e Gestão, 2018)
The business budget based on business objectives can represent the competitive advantage of Micro and Small Enterprises (SMEs). In this context, this study aims to elaborate and analyze the business budget in MPE industry of frames, in this study called Alfa. The methodology employed is linked to the quantitative-descriptive research, using the technical procedures of case study through documentary research and unstructured interview. The elaboration of the budget allowed to visualize the evolution of the economic efficiency of the Alpha industry in the budgeted period, especially in the period after the planned investment in the expansion of infrastructure. The main results show that the budgeting of the Alpha industry must observe the specific characteristics of the MEP, in particular those related to the limitations of financial resources, labor and time available. In addition, future forecasting should be carried out with caution and caution, through a flexible budget to adapt to market changes. The evaluation of the projected budget preserves the financial, assets and economic health of the alpha industry in the period from 2017 to 2021. Therefore, it is concluded that the elaboration and analysis of the budget in the alpha miter industry presents a contribution towards the implementation of the appropriate practices to its use and performance.